1993
DOI: 10.1093/jnci/85.15.1230
|View full text |Cite
|
Sign up to set email alerts
|

Stability of HER-2/neu Expression Over Time and at Multiple Metastatic Sites

Abstract: The fact that p185 immunoreactivity is rarely heterogeneous is encouraging, both for the potential use of HER-2/neu-related proteins as serum tumor markers and for innovative therapies targeted at p185 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
70
1
9

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 0 publications
5
70
1
9
Order By: Relevance
“…This result is in accordance with those concerning visceral metastases and local and regional metastases (Barnes et al, 1988;Niehans et al, 1993;Masood and Bui, 2000;Simon et al, 2001;Gancberg et al, 2002;Vincent-Salomon et al, 2002;Carlsson et al, 2004). Recently, in a meta-analysis of the published data concerning HER2 status stability among primaries and metastases, Carlsson et al (2004) confirmed that there was no drastic modification in HER2 status between primary tumours and their locoregional lymph node metastases and their distant visceral metastases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is in accordance with those concerning visceral metastases and local and regional metastases (Barnes et al, 1988;Niehans et al, 1993;Masood and Bui, 2000;Simon et al, 2001;Gancberg et al, 2002;Vincent-Salomon et al, 2002;Carlsson et al, 2004). Recently, in a meta-analysis of the published data concerning HER2 status stability among primaries and metastases, Carlsson et al (2004) confirmed that there was no drastic modification in HER2 status between primary tumours and their locoregional lymph node metastases and their distant visceral metastases.…”
Section: Discussionsupporting
confidence: 86%
“…HER2 status remains stable between the primary tumour site and distant metastasis (Niehans et al, 1993;Gancberg et al, 2002;VincentSalomon et al, 2002;Carlsson et al, 2004) or regional lymph node metastasis (Simon et al, 2001). In contrast, HER2 has been found to be overexpressed in 60 -100% in bone marrow micrometastatic cells, independently of the primary tumour status (Braun et al, 2001b).…”
mentioning
confidence: 99%
“…In most studies, concordance between primary tumour and distant metastases ranged between 87 and 100%. [32][33][34][35][36] Regitnig et al 13 found a newly occurring Her-2/neu amplification in metastases in 4 out of 18 cases (22%), 2 of which represented CNS metastases. In their series, Her-2/ neu-amplified primary tumours made up 14% of cases in the paired samples, which is different from our series consisting of brain-metastasizing tumours only.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5]23 For this last purpose, in the past 5 years the evaluation of HER-2 status was generally performed on the primary neoplasm, avoiding the biopsy of metastatic site, and in the assumption that the HER-2 status should remain stable in the years, as demonstrated in numerous previous studies, mostly based only on immunohistochemistry. [9][10][11]13,16,17 For this reason, to our knowledge, the necessity of HER-2 determination in metastatic lesion is not well established, at present time. 15 In this prospective study we have considered 119 pairs of primary tumours and their metastases subdivided in lymph node Cases with synchronous lymph node metastasis (group A), cases with metachronous lymph node metastasis (group B), cases with local recurrence (group C), cases with metachronous distant metastasis (group D).…”
Section: Discussionmentioning
confidence: 99%
“…Controversial opinions exist both about the stability of HER-2 status in breast carcinoma throughout the course of the disease, and about whether chemotherapy (neoadjuvant or adjuvant) can modify HER2 status. Most data have shown good overall concordance between primary and metastatic lesions, [9][10][11][12][13][14][15] but some data have demonstrated discordance in up to 20% of cases. 9,12,[16][17][18] These differences could be due to a possible genetic drift or clonal selection for HER-2, which may happen during tumour progression, 16 or to the presence of intratumoural heterogeneity of HER-2 status, [19][20][21] with a clone having enhanced metastatic potential, leading to metastases with different HER-2 status from that of the primary lesion.…”
mentioning
confidence: 99%